Errors in the Use of English Grammar - Giri, Anju (Journal of NELTA, 2011)
By systematically studying the errors committed by learners one can get a lot of hints about the learning strategies and mechanisms which they are employing in learning their target languages. Such hints have provided insights to the teachers, textbook writers, curriculum designers and many applied linguists and enable them to contribute to their fields. This article seeks to present a comprehensive study of grammatical errors committed by the bachelor level university students of Nepal learning English which followed the established stages of error analysis. It was found that the bachelor level students in Nepal did commit all sorts of grammatical errors in the use of the English language. For them, the error prone grammatical units were Sentence and Clause and the error prone grammatical categories were Conditionals, Mood, V-Form, Tense/Aspect, Main Verb, Subject-Verb Agreement, Question Formation, Auxiliary/Modal,Miscellaneous forms, 'So' Form, Determiner, Verb+Participle, Word Order, and Noun. Key words: Correct forms; Incorrect forms/mistakes; Errors Journal of NELTA Vol. 15 No. 1-2 December 2010 Page: 54-63 Uploaded date: 4 May, 2011 DOI: 10.3126/nelta.v15i1-2.4610